Policy-it from just-in-time integration to web services. - Boubez, Toufic
Business has long pursued the goal of making IT more of a strategic tool and less of a necessary eveil. Organizations are constantly looking for easier, cheaper and more logical ways to build applications and unite the silos of functionality they still depend on. One approach that has met with some sucess is the concept of just-in-time integration-a technique to combine new functionalities as quickly and cheaply as required, whether they reside inside an organization or outside of it (i.e., with a business partner).